Granularity-aware legal question answering: a case study of Indonesian government regulations - Faisal, Douglas Raevan; Darari, Fariz; Ryanda, Reynard Adha (International Journal of Advances in Intelligent Informatics, 2024)
Question answering (QA) technologies are crucial for building conversational AI.Â  Current research related to QA for the legal domain lacks focus on the organized structure of laws, which are hierarchically segmented into components at varying levels of detail. To address this gap, we propose a new task of granularity-aware legal QA, which accounts for the underlying granularity levels of law components. Our approach encompasses task formulation, dataset creation, and model development. Under the Indonesian jurisdiction, we consider four law component granularity levels: chapters (bab), articles (pasal), sections (ayat), and letters (huruf). We include 15 government regulations (Peraturan Pemerintah) of Indonesia related to labor affairs and build a legal QA dataset with granularity information. We then design a solution for such a taskâ€”the first IR system to account for legal component granularity. We implement a customized retriever-reranker pipeline in which the retriever accepts law components of multiple granularities and the reranker is trained for granularity-aware ranking. We leverage BM25 and BERT models as retriever and reranker, respectively, yielding an end-to-end exact match accuracy of 35.68%, which offers a significant improvement (20%) over a strong baseline. The use of reranker also improves the granularity accuracy from 44.86% to 63.24%. In practical context, such a solution can help provide more precise answers, not only from legal chatbots, but also other conversational AI that deals with hierarchically-structured documents.